Perancangan Aplikasi Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) Berbasis Web - Leo Nelson Barce Rumayom; Jasson Prestiliano; Mila C. Paseleng (Universitas Kristen Duta Wacana, 2013)
Team Games Tournament (TGT) as one of cooperative learning models could increase students skills but, this learning model need much time in implementation like grouping students and calculating tournament points. Web based cooperative learning application that designed in this research using TGT model. This application simplify implementation of TGT model because, students grouping will done in virtual mode and the application will automatically calculate tournament points. This application easy in use and quite effective.